Population dinamics of Lymnaea rubiginosa in rice fields and its infection with larvae of trematodes - Suhardono .; D.B Copeman (Indonesian Center for Animal Research and Development (ICARD), 2000)
Field of irrigated rice paddy was the most suitable habitat as breeding site of snail Lymnaea rubiginosa, the intermadiate host of Fasciola gigantica and other trematodes. Fluctuations in the population of fresh water snail, L. rubiginosa in irrigated rice fields and their infection with L. rubiginosa and other trematodes were studied in five villages in the subdistrict of Surade, provivine of West Java. Snail were sampled based on time collection (half man hour) each site of collection. The samples of the snails were further counted and examined for the presence of larval trematodes. The result indicated that snails died during the dry season except those in persistent aquatic refuges such as streams and springs. Surviving snails recolonised rice fields near villages by passive transfer with water from refuges early in the wet season. Some recolonosation may also have resulted from haching of snail eggs deposited in habitats which had not been dried for more than a few weeks. Recolonisation with snails of further rice fields from a village occurred during the later period of the wet season. No snail infected with F. gigantica was found in the distance of more than 200 m from a village. Snail with the highest prevalence of infection occurred in rice fields which received effluent from a cattle pen were fertilised with bovine faeces. Each snail was only infected with one species of tramatodes. Infection with echinostone larvae was most common. Kay words: L. rubiginosa, trematode infection, population dynamic